Relationship between color and antioxidant capacity of fruits and vegetables - Cömert, Ezgi Doğan (Curr Res Food Sci, 2019)
Visual perception plays a key role in the selection of nutritious and healthy foods. Color, as one of the most important senses of vision, can be used as an indicator of food quality/defects and grade. It is recommended consumers include various colors in their plate to obtain various vitamins and minerals. Color is also thought to be related to antioxidant capacity. Within this regard, this study investigated the relationship between color and antioxidant capacity in various fruits and vegetables. The results indicate the color hues analyzed by computer vision based image analysis can be related with TAC of fruits and vegetables, but with some limitations and can be used as a guide for food selection to increase daily antioxidant intake. Most of fruits and vegetables having hue values above 180° and below 20°, have high antioxidant capacity (>10 mmol TE/kg fresh weight). The results also emphasized the importance of the serving size of fruits and vegetables in terms of their contribution to daily antioxidant intake. Based on these results, fruits and vegetables could be categorized into low-, medium-, and high-antioxidant groups according to their TAC and potential contributions to fulfill the recommended daily antioxidant intake. Finally, daily antioxidant intake was evaluated with a healthier scenario created by doubling vegetable portion and reducing fruit portion by half in the meal.